The story of promiscuous crucifers: origin and genome evolution of an invasive species, Cardamine occulta (Brassicaceae), and its relatives - Mandáková, Terezie; Zozomová-Lihová, Judita; Kudoh, Hiroshi; Zhao, Yunpeng; Lysak, Martin A; Marhold, Karol (Annals of botany, 2019)
BACKGROUND AND AIMS: Cardamine occulta (Brassicaceae) is an octoploid weedy species (2n = 8x = 64) originated in Eastern Asia. It has been introduced to other continents including Europe and considered to be an invasive species. Despite its wide distribution, the polyploid origin of C. occulta remained unexplored. The feasibility of comparative chromosome painting (CCP) in crucifers allowed us to elucidate the origin and genome evolution in Cardamine species. We aimed to investigate the genome structure of C. occulta in comparison with its tetraploid (2n = 4x = 32, C. kokaiensis and C. scutata) and octoploid (2n = 8x = 64, C. dentipetala) relatives. METHODS: Genomic in situ hybridization (GISH) and large-scale CCP were applied to uncover the parental genomes and chromosome composition of the investigated Cardamine species. KEY RESULTS: All investigated species descended from a common ancestral Cardamine genome (n = 8), structurally resembling the Ancestral Crucifer Karyotype (n = 8), but differentiated by a translocation between chromosomes AK6 and AK8. Allotetraploid C. scutata originated by hybridization between two diploid species, C. parviflora and C. amara (2n = 2x = 16). By contrast, C. kokaiensis has an autotetraploid origin from a parental genome related to C. parviflora. Interestingly, octoploid C. occulta probably originated through hybridization between the tetraploids C. scutata and C. kokaiensis. The octoploid genome of C. dentipetala probably originated from C. scutata via autopolyploidization. Except for five species-specific centromere repositionings and one pericentric inversion post-dating the polyploidization events, the parental subgenomes remained stable in the tetra- and octoploids. CONCLUSIONS: Comparative genome structure, origin and evolutionary history was reconstructed in C. occulta and related species. For the first time, whole-genome cytogenomic maps were established for octoploid plants. Post-polyploid evolution in Asian Cardamine polyploids has not been associated with descending dysploidy and intergenomic rearrangements. The combination of different parental (sub)genomes adapted to distinct habitats provides an evolutionary advantage to newly formed polyploids by occupying new ecological niches.
Keywords: polyploidie; Cardamine; Dálný východ; Polyploidy; lidé; Europe; Asia, Eastern; Evropa; Brassicaceae; Introduced Species; zavlečené druhy; genom rostlinný; Genome, Plant; Humans